(untitled) (International Journal of Food and Nutritional Sciences, 2022)
The pure and sodium chloride doped thiourea crystals were grown at low temperature by slow evaporation technique. The effect of the dopand concentration on the morphology and hence the structure was studied. The in corporation of sodium chloride in the mother solution was found to change the growth habits. The habit of the crystals changed from hexagonal to rhombohedral.